2008
DOI: 10.1166/jnn.2008.174
|View full text |Cite
|
Sign up to set email alerts
|

γ-Radiation Synthesis and Properties of Superparamagnetic CS-ZnSe:Mn Nanocrystals for Biological Labeling

Abstract: Chitosan coated ZnSe:Mn (CS-ZnSe:Mn) nanocrystals were successfully synthesized in aqueous system through a gamma-radiation route at room temperature under ambient pressure. The structure and properties of nanocrystals were investigated with transmission electron microscope (TEM), fourier transform infrared spectrometer (FT-IR), ultraviolet-visible (UV-vis) spectrometer, photoluminescence emission (PL) spectra, X-ray Diffraction (XRD) and energy dispersion spectrum (EDS). Results showed that the diameter of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…290 Use of a polysaccharide-coating is an effective way to improve the biocompatibility of Mn-doped QDs in the cellular environment. Kang et al 291 used g-radiation to graft chitosan on the surface of Mn-doped ZnSe QDs, and found that the synthesized chitosan-coated Mn-doped ZnSe QDs stained cytoplasm but did not enter into nucleus after Hep G2 cells were incubated in the solution of QDs. Chitosan-coated Mn-doped ZnS QDs also show very similar intracellular behavior.…”
Section: Doped Qds For Bioimagingmentioning
confidence: 99%
“…290 Use of a polysaccharide-coating is an effective way to improve the biocompatibility of Mn-doped QDs in the cellular environment. Kang et al 291 used g-radiation to graft chitosan on the surface of Mn-doped ZnSe QDs, and found that the synthesized chitosan-coated Mn-doped ZnSe QDs stained cytoplasm but did not enter into nucleus after Hep G2 cells were incubated in the solution of QDs. Chitosan-coated Mn-doped ZnS QDs also show very similar intracellular behavior.…”
Section: Doped Qds For Bioimagingmentioning
confidence: 99%
“…12 In the next year, Norris et al 13 developed an organometallic synthesis method to prepare highquality ZnSe nanocrystals doped with Mn impurities. Then, Dai et al 14 reported the g-radiation synthesis of superparamagnetic CS-ZnSe:Mn nanocrystals which were utilized for biological labeling. Recently, the organometallic synthesis of Mn:ZnSe d-dots achieved a great breakthrough; 5-8 Peng's group decoupled the doping process from nucleation and/or growth, and designed nucleation-doping and growth-doping processes to prepare Mn:ZnSe d-dots and Cu:ZnSe d-dots, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…There have been various synthetic approaches reported in synthesis of doped QDs [16][17][18][19][20][21][22][23][24] and several good reviews or research articles on this subject [11,[25][26][27][28][29][30]. In 2001, Norris et al [16] first demonstrated successful doping of Mn 2 + into ZnSe colloidal nanocrystals through organometallic synthesis at 240-300 1C.…”
Section: Introductionmentioning
confidence: 99%